2019
DOI: 10.1590/1678-9865201932e190042
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of elderly assisted in primary care and their relationship with social determinants of health

Abstract: Objective To review the influence of social determinants of health in the nutritional status of the elderly assisted in a primary care Unit in a Recife, Pernambuco, Brazil, community. Methods This was a cross-sectional study with an analytical approach. The universe was composed of 129 elderly attending a family health unit in Recife, Pernambuco, Brazil. The data were collected according to a protocol. The effect of the association of independent variables with the body mass index was estimated using hierarch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Malnutrition is a complex and multidimensional problem, in which several determinants (psychosocial health, physical state, lifestyle, and eating habits) interact with each other [9,29]. In this study, malnutrition, the risk of malnutrition, and weight and appetite loss in long-lived older people were associated with several health factors.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Malnutrition is a complex and multidimensional problem, in which several determinants (psychosocial health, physical state, lifestyle, and eating habits) interact with each other [9,29]. In this study, malnutrition, the risk of malnutrition, and weight and appetite loss in long-lived older people were associated with several health factors.…”
Section: Discussionmentioning
confidence: 74%
“…A systematic review and meta-analysis with 240 studies with older adults using the MNA identified that the prevalence varies according to the setting, from 3.1% in the community to 29.4% in rehabilitation services and subacute care facilities for malnutrition; and from 26.5% in the community to 49% in long-term care facilities for the risk of malnutrition [15]. In Brazil, studies show a prevalence of 45.3% for risk of malnutrition and 3.1% for malnutrition; 28.3% and 38.76% for risk of malnutrition [9,30,31]. In Italy, 34.2% were at risk and 14.8% malnourished [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os problemas de saúde mais comuns incluíram Hipertensão Arterial Sistêmica (HAS), relatada por 72% dos participantes, seguida por Diabetes Mellitus (DM), presente em 29% dos casos, e Dislipidemia, observada em 37% da amostra. Estudos anteriores corroboram essa alta prevalência, como o de Bandeira; Moreira; Silva (2019), que identificaram a presença de HAS em 98% e DM em 34% dos idosos em uma Clínica da Família em Recife (Bandeira;Moreira;Silva, 2019). Resultados semelhantes foram encontrados por Barroso et al (2020), que verificou adequação da ingestão de macronutrientes e micronutrientes e o estado nutricional de idosos frequentadores do centro de atenção à saúde do idoso e cuidador da UFF, com uma prevalência de 76% de HAS, 38% de DM e 29,5% de Dislipidemia em sua pesquisa (Barroso et al, 2020).…”
Section: Resultsunclassified
“…A renda é o principal fator que interfere no acesso e obtenção de alimentos (Bandeira;Moreira;Silva, 2019;Geib, 2012), os resultados demonstram que idosos com menor renda possui reduzido poder de compra de alimentos com elevado custo como frutas, verduras, legumes e laticínios. Os nutrientes encontrados nos grupos alimentares desempenham papéis fundamentais na manutenção da saúde e no funcionamento adequado do corpo humano.…”
Section: Resultsunclassified